2010
DOI: 10.1590/s2236-89062010000300002
|View full text |Cite
|
Sign up to set email alerts
|

Macroalgas em nascentes e arredores de riachos na região noroeste do estado de São Paulo

Abstract: -(Macroalgae in springs and surrounding streams of northwestern region of São Paulo State). Macroalgae are typically benthic organisms that a mature, discreet and recognizable naked eye thallus, and microscopic identification is necessary. Several studies have been carried out aiming to the taxonomic knowledge in Brazilian streams, however works dealing with algae from springs are rare. Monthly sampling were carried out from February to September/2007 in springs and the surrounding (humid soil near the springs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The total number of taxa found in the present study (38) can be considered high when compared to studies carried out in other Brazilian regions that used similar methodology, namely: i) 13 taxa (Pereira & Branco 2010) and 21 taxa (Almeida et al 2011) in the northwest of the São Paulo State; ii) 23 taxa (Branco et al 2008) and 34 taxa , in the central-southern region of the Paraná State; iii) 24 taxa (Branco et al 2009) in the mid-western region of the Paraná State, and; iv) 19 taxa (Peres et al 2008) reported to the eastern region of Paraná State. Likewise, when considering the relative richness, found 1.81 taxa per sampling point, which is also higher when compared to what was reported in those other regions (taxa per sampling point and respective studies: 1.09 in Branco et al 2009, 1.23 in Almeida et al 2011, 1.35 in Peres et al 2008, 1.78 in Krupek et al 2008, 2.09 in Branco et al 2008.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The total number of taxa found in the present study (38) can be considered high when compared to studies carried out in other Brazilian regions that used similar methodology, namely: i) 13 taxa (Pereira & Branco 2010) and 21 taxa (Almeida et al 2011) in the northwest of the São Paulo State; ii) 23 taxa (Branco et al 2008) and 34 taxa , in the central-southern region of the Paraná State; iii) 24 taxa (Branco et al 2009) in the mid-western region of the Paraná State, and; iv) 19 taxa (Peres et al 2008) reported to the eastern region of Paraná State. Likewise, when considering the relative richness, found 1.81 taxa per sampling point, which is also higher when compared to what was reported in those other regions (taxa per sampling point and respective studies: 1.09 in Branco et al 2009, 1.23 in Almeida et al 2011, 1.35 in Peres et al 2008, 1.78 in Krupek et al 2008, 2.09 in Branco et al 2008.…”
Section: Discussionmentioning
confidence: 53%
“…Particularly for stream macroalgae (sensu Sheath & Cole 1992), the floristic surveys have focused basically only the Southeastern (Branco & Necchi Júnior 1996, Pereira & Branco 2010, Almeida et al 2011 and Southern regions of Brazil (Krupek et al 2008, 2009. Although these efforts have contributed profoundly to the knowledge of Brazilian flora, there is a huge gap in the knowledge of the distribution of organisms throughout the territory, thus clearly contributing to the Wallacean shortfall in the group.…”
Section: Introductionmentioning
confidence: 99%